Fluoride Levels in Drinking Water Across Lahore District Towns and Their Link to Dental Fluorosis (2022) - Asif, Komal; Saleem, Ssba; Asif, Rabeet; Farooq, Muhammad Umer; Razzaq, Anjum (Journal of University College of Medicine and Dentistry, 2024)
Objective: To measure the concentration of fluoride levels in drinking water and its association with dental fluorosis in various towns of Lahore district, Pakistan in the year 2022. Methods: This descriptive cross-sectional study was conducted from 27th September to 30th December, 2022 across nine towns in Lahore, where 100 drinking water samples were collected from randomly selected tube wells. The tube wells were chosen using random number tables from a list provided by WASA. Additionally, 400 residents aged 25 years and above (4 residents per area) were interviewed and clinically examined for dental fluorosis in the areas corresponding to the water sample collection sites. Fluoride concentrations in all water samples were analyzed using the spectrophotometric method at the Pakistan Council of Research in Water Resources (PCRWR) laboratory in Lahore. Results: With 1.5 mg/l as the recommended fluoride level in drinking water, the fluoride concentration ranged from 0.50 to 1.63 mg/l, with a mean of 0.58 ± 0.33 mg/l among individuals with dental fluorosis compared to those without. This difference was statistically significant (p = 0.013). Dental fluorosis was observed in 189 participants (47.3%), of whom 48.8% were male and 39.7% were female. Conclusion: Fluoride levels in drinking water exceeding the recommended limit were significantly associated with a higher frequency of dental fluorosis among residents. Keywords: Fluoride concentration, Drinking water, Dental fluorosis, Dean’s fluorosis index, tube-wells.